Doing (In)Justice? Cairene Place Naming and Politics of Forgetting - Saad, Sadek (Advances in Social Sciences Research Journal, 2024)
Toponym is a crucial part of the city’s symbolic meanings. Its investigation explores what is said or unsaid about the past and explains memory operation. Cairo experienced multiple cases of naming and renaming throughout its history; however, whose history is remembered, misremembered, or forgotten? The author argues that Cairene’s toponym is used as a tool for the politics of dictated forgetting and misremembering. The study explores the Cairene naming and renaming politics processes in three significant eras: Historic Cairo (before 1800), Royal Cairo (1840-1950), and Pretorian Cairo (after 1956). Such an investigation aims to comprehend the authorities’ naming and renaming impact on the Cairo memorial landscape. Decoding the Cairene memorial landscape demands an interdisciplinary study. Urban sociology analyses history as a data source for creating models; urban geography deals with the city on its fundamental level, and urban history searches for events’ meanings and consequences for the city. Focusing on what is accessible and observable in the Cairene memorial landscape suggests finding the best alternative conclusion. While places in historic Cairo were named by identities, Royal and Pretorian Cairo introduced toponyms for manipulating public memory.